Strategi Pengelolaan Drainase Pasar Tradisional Palapa di Kota Pekanbaru - Nurdin Nashrul Haq; Zulkarnaini Zulkarnaini; Suardi Tarumun (Dinamika Lingkungan Indonesia, 2015)
This research was conducted in Mei to July 2014 in Palapa Tradional Market,Durian Street, East Labuhbaru, Payung Sekaki Sub-district, Pekanbaru. The purpose of thisresearch is to analyze the government policy in drainage market management of Palapatraditional market in pekanbaru, to identify strength, weakness, opportunity and threat ofPalapa traditional market management in Pekanbaru. Formulate drainage managementstrategy of Palapa Traditional Market in Pekanbaru. The data was collected qualitatively byusing interview, observation and survey. The data was analyzed by using SWOT analysis. Thestrategy of Palapa Traditional Market management is to increase the drainage infrastructuresystem of Palapa market activity the efforts to improve drainage quality of Palapa TraditionalMarket. the efforts to improve performance quality of market UPTD toward drainage toevaluate the government policy in drainage management. The efforts to increase drainageservice system by establishing new drainage or widening old drainage to evoke the traderparticipation in maintenance operation of market drainage canals. To make a drainage planaccurately based on the drainage technique to establish the regulation and institution thatoversee the drainage management system and to punish drainage destroyer.